The Impact of Social Reality on Family Communication: An Analytical Theoretical Study - Mohammad Omar AL-Momani; Elham Mahmoud Rababa (Jurnal Pendidikan Ilmu Sosial, 2023)
Exposed And exposed families for several from the changes which I inherited it some Appearances Weakness that may be Pay with it to collapse, Lost exposed family to effect transitions Economic social and cultural that I yielded she has during practical development overall And that did not be to fit in And reality families in times a lot when I created it from patterns strange, command that led to Appearance of the several from phenomena negative and perverted which affected on effectiveness Different institutions the society and family as a highlighted This is amazing institutions; Therefore, this study came, which aimed to identify the social reality and its impact on family communication, where the theoretical narrative approach was used, which discusses the problem and deals with it from its various aspects. Form Al-Qaeda the basic in structure any Community, In addition to the need to confront risks Change constant on the family, In addition to the need to pay attention to interaction and engagements family And pay attention to the process Connection The family that continue its importance Bezel life which necessity to achieve Compatibility profile Which contribute to reducing the level of rebuke router for children And rule culture dialogue.